Litterfall carbon cycle in pine stands growing in the Central Siberian subtaiga forest-steppe zone - Melnik Alexandra; Chanchikova Svetlana; Vais Andrey; Nemich Victor; Mikhaylov Pavel (E3S Web of Conferences, 2023)
The article presents the methodology of collection and desk study of forest litterfall samples. The fractional composition of woody debris has been studied. Biomass and carbon stocks in pine stands litter have been estimated.